Енергетичний спектр псевдоспiн-електронної моделi в методi динамiчного середнього поля - Stasyuk, I. V.; Krasnov, V. O. (Publishing house "Academperiodika", 2018)
The pseudospin-electron model in the case of infinite on-site electron repulsion is investigated. The electron energy spectrum is calculated within the framework of the dynamical mean field theory (DMFT), and the alloy analogy approximation is developed. The effect of the pseudospin-electron interaction, local asymmetry field, and tunneling-like level splitting on the existence and the number of electron subbands is investigated. The relation of the pseudospin-electron model to the problem of energy spectrum of boson-fermion mixtures in optical lattices is discussed.